Shooting accuracy in children`s basketball: Do equipment dimensions influence static and dynamic performances? - Milovanovic, M. Z.; Pažin, N. R.; Mrdakovic, V. D.; Erculj, F. F.; Jakovljevic, S. T. (Journal of Sports Sciences, 2020)
The purpose of study was to explore the influence of equipment dimensions on shooting accuracy in children`s basketball through the effects of (a) using basket height and ball size for children and adult, along with different shooting distances (Study 1) and (b) the applied 12-week shooting training with different ball sizes (Study 2). The participants were basketball players from the same club ages from 10 to 11 years and with at least one-year basketball training experiences. In Study 1, we recruited 22 children; while in Study 2 we selected 36 children in two experimental (practice with balls for adults and children) and one control group (no practice). Shooting accuracy was assessed through the static and dynamic trials. The obtained results showed that children equipment provided no acute advantages compared to the adult equipment in terms of shooting accuracy either in static or dynamic conditions. In addition, we found no benefits on shooting accuracy when compared the effects of applied shooting training either for practice with children`s or adult`s ball sizes. The present findings suggested that the applied manipulations of equipment for children and adult produce no differences in terms of static or dynamic shooting accuracy performances in young basketball players.